A new species of Ooencyrtus Ashmead (Hymenoptera: Encyrtidae), parasitoid on pupae of Xenasteia sp. (Diptera: Xenasteiidae) from Karnataka, India - Hayat, Mohammad; Gupta, Ankita; Selvaraj, Krishnan (Zootaxa, 2018)
A new species of Ooencyrtus Ashmead (Hymenoptera: Encyrtidae), O. xenasteiae Hayat & Gupta, sp. nov., is described. This species was reared from the pupae of a Xenasteia sp. (Diptera: Xenasteiidae), a sooty mould scavenger found associated with the recent invasive rugose spiralling whitefly, Aleurodicus rugioperculatus Martin (Hemiptera: Aleyrodidae) from coastal Karnataka, India.